Adoption workers' perspectives on adoption adjustment and the honeymoon period. (December 2020) - Goodwin, Bonni; Madden, Elissa; Singletary, Jon; Scales, T. Laine
Highlights: Model of adoption adjustment suggested with times of increased risk for breakdown. Improved post-adoption support using specific timeframes within adoption adjustment. Adoption specialized training is critical for professionals supporting adoption. Abstract: The process of adopting a child holds specific challenges for a new adoptive family. When a child joins an adoptive family, the adjustment necessary for each family member plays a significant role in the outcome of the placement. Yet, despite the importance that adjustment plays in the success of an adoption, very few studies have focused on the adjustment process or the "honeymoon period" for children and families. This study offers valuable insight into various aspects of healthy adoption adjustment and the honeymoon period and provides a foundation for a model of adoption adjustment with specific time frames and insight into when the most challenges to healthy adjustment arise. Implications for practice include tools and strategies for adoption workers in child welfare to monitor adoption adjustment more closely.